Evaluación vascular y efecto hipotensor de plantas del género marila - Morán Pinzón, Juan (2008)
This study was designed to investigate the cardiovascular effect of different extracts from Marila laxiflora and Marila pluricostata, which belong to Marila genus.On aortic rings from Sprague-Dawley male rats (250-270g) contracted by phenylephrine (PE 1X10-6 M) all extracts assayed, induced a concentration-dependent relaxation, however dichloromethanic  extract from leaves of Marila pluricostata (H-CH2Cl2) showed the higher vasorelaxant effect (95.60± 2.40%) while the methanolic extract from M. laxiflora (R-MeOH) reached an effect of 63.49 ± 3.07%.In other experiments, our group has investigated the hypotensive activity of a single dose (150 mg/Kg) by intraperitoneal administration of extracts with higher vasorelaxant effect using tail-cuff technique in unanesthetized spontaneous hypertensive rats.Extracts from M. laxiflora caused a poor hypotensive effect during first hour, while extracts from M. pluricostata showed a significative hypotensive response which was observed until six hours after administration.On pharmacological point of view, our results have suggested that chemical compounds present on extracts from Marila genus plants could have an interesting profile of cardiovascular activity.